2010
DOI: 10.1016/j.clinimag.2009.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary tumor of the pancreas in children: typical radiological findings and pathological correlation

Abstract: We report a case series of three children with solid pseudopapillary tumor of the pancreas (SPT) in which a complete radiological work-up, including ultrasound, computed tomography scans, and MRI, has been carried out. The aim of this article is to highlight the characteristic imaging findings of SPT in the pediatric age group and to establish a correlation with typical histopathological findings of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Notably, 8 of our patients were younger than 18 years (15.6%), in keeping with other reports in the literature that have suggested that SPN may account for 8% to 16.6% of pancreatic tumors in children. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, 8 of our patients were younger than 18 years (15.6%), in keeping with other reports in the literature that have suggested that SPN may account for 8% to 16.6% of pancreatic tumors in children. 16 …”
Section: Discussionmentioning
confidence: 99%
“…MRI should be considered the best imaging technique for children due to the absence of radiation and its improved capacity for visualizing tumor components, especially intratumoral areas of hemorrhage. Both the fibrous capsule and the intramural hemorrhage are important clues for the final diagnosis because they are rarely found in other pancreatic neoplasms [16].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the patient was diagnosed as SPT after typical CT scan appearance with clinical history of a young girl. MRI is the best imaging technique for children due to reduce risk of radiation and better visualisation of central haemorrhage 17. Both central haemorrhage and peripheral fibrous pseudocapsule (heterogenous signal intensity in T2-weighted image and low signal intensity in T1-weighted image, but usually enhance after gadolinium application) are important findings or correct diagnosis because the features are very unusual in other pancreatic tumours 17…”
Section: Discussionmentioning
confidence: 99%